Myocardial Gene Expression of T-bet, GATA-3, Ror-γt, FoxP3, and Hallmark Cytokines in Chronic Chagas Disease Cardiomyopathy: An Essentially Unopposed TH1-Type Response - Luciana Gabriel Nogueira; Ronaldo Honorato Barros Santos; Alfredo Inácio Fiorelli; Eliane Conti Mairena; Luiz Alberto Benvenuti; Edimar Alcides Bocchi; Noedir Antonio Stolf; Jorge Kalil; Edecio Cunha-Neto (Mediators of Inflammation)
Background. Chronic Chagas disease cardiomyopathy (CCC), a late consequence of Trypanosoma cruzi infection, is an inflammatory cardiomyopathy with prognosis worse than those of noninflammatory etiology (NIC). Although the T cell-rich myocarditis is known to play a pathogenetic role, the relative contribution of each of the functional T cell subsets has never been thoroughly investigated. We therefore assessed gene expression of cytokines and transcription factors involved in differentiation and effector function of each functional T cell subset (TH1/TH2/TH17/Treg) in CCC, NIC, and heart donor myocardial samples. Methods and Results. Quantitative PCR showed markedly upregulated expression of IFN-γ and transcription factor T-bet, and minor increases of GATA-3; FoxP3 and CTLA-4; IL-17 and IL-18 in CCC as compared with NIC samples. Conversely, cytokines expressed by TH2 cells (IL-4, IL-5, and IL-13) or associated with Treg (TGF-β and IL-10) were not upregulated in CCC myocardium. Expression of TH1-related genes such as T-bet, IFN-γ, and IL-18 correlated with ventricular dilation, FoxP3, and CTLA-4. Conclusions. Results are consistent with a strong local TH1-mediated response in most samples, possibly associated with pathological myocardial remodeling, and a proportionally smaller FoxP3+CTLA4+ Treg cell population, which is unable to completely curb IFN-γ production in CCC myocardium, therefore fueling inflammation.